A Highly Crystalline Manganese‐Doped Iron Oxide Nanocontainer with Predesigned Void Volume and Shape for Theranostic Applications. (3rd May 2013) - Phan, Vu Ngoc; Lim, Eun‐Kyung; Kim, Taekhoon; Kim, Minsik; Choi, Yuna; Kim, Byeongyoon; Lee, Myounghoon; Oh, Aram; Jin, Juhong; Chae, Youngjoo; Baik, Hionsuck; Suh, Jin‐Suck; et al.
<x xml:space="preserve">Abstract</x> Hollow Mn‐doped iron oxide nanocontainers, formed by a novel one‐pot synthetic process, fulfill the dual requirements of delivering an effective dose of an anticancer drug to tumor tissue and enabling image‐contrast monitoring of the nanocontainer fate through T2‐weighted magnetic resonance imaging, thereby determining the optimal balance between diagnostic and therapeutic moieties in an all‐in‐one theranostic nanoplatform. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>